2021
DOI: 10.1038/s41598-021-85531-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D deficiency on the improvement of metabolic disorders in obese mice after vertical sleeve gastrectomy

Abstract: Vertical sleeve gastrectomy (VSG) is one of the most commonly performed clinical bariatric surgeries for the remission of obesity and diabetes. Its effects include weight loss, improved insulin resistance, and the improvement of hepatic steatosis. Epidemiologic studies demonstrated that vitamin D deficiency (VDD) is associated with many diseases, including obesity. To explore the role of vitamin D in metabolic disorders for patients with obesity after VSG. We established a murine model of diet-induced obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 71 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…The authors revealed that, despite known beneficial effects induced by the surgery itself, deficient levels of vitamin D were associated with limited improvements of the gut dysbiosis induced by the high‐fat diet feeding. Indeed, the effects of the surgery, a decrease of Firmicutes and an increase of Bacteroidetes phyla abundance, were weaker in the group of vitamin‐D‐deficient animals post‐surgery in comparison with the group with normal levels of vitamin D 30 …”
Section: Consequence Of Vitamin Deficiencies On Gm Compositionmentioning
confidence: 92%
See 3 more Smart Citations
“…The authors revealed that, despite known beneficial effects induced by the surgery itself, deficient levels of vitamin D were associated with limited improvements of the gut dysbiosis induced by the high‐fat diet feeding. Indeed, the effects of the surgery, a decrease of Firmicutes and an increase of Bacteroidetes phyla abundance, were weaker in the group of vitamin‐D‐deficient animals post‐surgery in comparison with the group with normal levels of vitamin D 30 …”
Section: Consequence Of Vitamin Deficiencies On Gm Compositionmentioning
confidence: 92%
“…29 as well as with increased intestinal inflammation and permeability. 30 In addition to those metabolic observations regarding vitamin D, many studies also reported strong links of this vitamin with adipose tissue in terms of vitamin D storage but also modulation of adipocyte differentiation or even energy metabolism and inflammation by this vitamin.…”
Section: Evidence Of Vitamin Deficiency In Obesity and Related Metabo...mentioning
confidence: 95%
See 2 more Smart Citations